Malacoplakia of the bladder combined with infected renal calculi: A case report - He, Qunjun; Wang, Yi; Chen, Xian; Xia, Baopiao; Zeng, Xuqiang; Wang, Binhui; Fang, Yong; Liu, Shulin; Xu, Wujun (Frontiers in Surgery, 2023)
The malacoplakia of the bladder is a rare chronic acquired infection- associated granulomatous disease and even less common in combination with urinary stones. We report the case of a 58-year-old female patient with malacoplakia of the bladder combined with renal calculi. The patient was admitted to the hospital with bilateral low back pain for one month and space-occupying lesions of the bladder for three days. Preoperative imaging suggested space-occupying lesions of the bladder: high probability of bladder cancer. Following the anti-infection treatment, the transurethral electrodesiccation was performed on the space-occupying lesions of the bladder. Pathological examination confirmed the diagnosis of malacoplakia of the bladder. Left-sided percutaneous nephrolithotomy was performed electively to remove the predisposing factors of infection. After the operation, the patient continued to receive anti-infection treatment for two months. The patient had a good prognosis in the six-month follow-up. Malacoplakia of the bladder is easily misdiagnosed as bladder cancer before operation, and the diagnosis depends on pathological diagnosis. Complete removal of urinary calculi, infection and other inducing factors, is beneficial to the treatment of malacoplakia of the bladder.